1937
DOI: 10.1152/ajplegacy.1937.119.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgenic Substances in Hypophysectomized Rats

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1938
1938
1974
1974

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Rubinstein (8) has reported a certain amount of stimulation of the germinal epithelium in testosterone treated immature rats. Testosterone pro' pionate as well as other androgens are capable of maintaining spermatogenesis in the hypophysectomized rat (14,15). Even though some doubts as to the specificity of this action have been voiced (16), a dual action of testosterone propionate would offer a tentative explanation for our results.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Rubinstein (8) has reported a certain amount of stimulation of the germinal epithelium in testosterone treated immature rats. Testosterone pro' pionate as well as other androgens are capable of maintaining spermatogenesis in the hypophysectomized rat (14,15). Even though some doubts as to the specificity of this action have been voiced (16), a dual action of testosterone propionate would offer a tentative explanation for our results.…”
Section: Discussionmentioning
confidence: 63%
“…Rubinstein and Abarbanel (22) found that sheep's pituitary extract stimulates both the germinal cells and the interstitial tissue. It seems of interest, in view of our findings, that androgens should be capable of main' taining spermatogenesis in the hypophysectomized rats but failed to maintain the interstitial tissue (14).…”
Section: Discussionmentioning
confidence: 77%
“…Thus the failure of the cases under discussion to demonstrate such a rise is evidence against increased hypophyseal activity. Since testosterone has a gonadotropic action in maintaining spermatogenesis in the hypophysectomized animal (27), another possibility is that methyl testosterone may imitate other hypophyseal hormonal effects, namely, upon nitrogen metabolism.…”
Section: Commentmentioning
confidence: 99%
“…This hormone therapy invariably prevented post-operative regression of the seminiferous epithelium (Walsh et al, 1934;Nelson and Gallagber, 1936;Nelson, 1937Nelson, , 1940Nelson and Merkel, 1938;Cutuly et al, 1937;Cutuly, 1941Cutuly, , 1952Wells, 1942;Dv"oskin, 1943;Gearenstroom and de Jongh, 1946).…”
Section: Effects Of Hormones On the Testismentioning
confidence: 98%